Mercy Watson goes for a ride - DiCamillo, Kate (DiCamillo, Kate. Mercy Watson, 2006)
Mr. Watson's usual Saturday drive in his Cadillac with his favorite pig, Mercy, turns into an adventure when an unexpected passenger shows up in the back seat and Mercy finds herself behind the wheel.